Linkage to the FOXC2 region of chromosome 16 for varicose veins in otherwise healthy, unselected sibling pairs. Issue 3 (2nd March 2005) - Ng, M Y M; Andrew, T; Spector, T D; Jeffery, S
Abstract : Background: The FOXC2 gene on 16q24 is mutated in lymphoedema distichiasis (LD), in which varicose veins (VV) are a common feature. We hypothesised that this gene might be implicated in the development of VV in the normal population, therefore, after performing a classical twin study, we tested for linkage and association in white women. We also tested for linkage with haemorrhoids (H), as a separate venous anomaly at the same locus. Methods: A total of 2060 complete female twin pairs aged 18–80 years from the St Thomas' Adult UK Twin registry replied to questions on VV and H as part of a broader postal survey of 6600 twins (62% response rate). Dizygotic female twin pairs were tested for linkage and association to the candidate marker D16S520 (1903 individuals genotyped), which is located about 80 kb from FOXC2 . Results: Casewise concordance rates were significantly higher for monozygotic than dizygotic twins for both phenotypes (VV 67% v 45%; p = 2.2×10 −6 ; H 68% v 59%; p = 0.01; H including during pregnancy 73% v 64%; p = 2.1×10 −4 ), corresponding to additive genetic heritabilities in liability of 86% (95% confidence interval (CI) 73% to 99%) for VV and 56–61% for H (95% CI 43% to 73%). The presence of VV and H were significantly correlated. We found significant evidence of linkage to the marker for VV (MLSASP = 1.37, p = 0.01; GLMASP/DSP Z = 3.17 p = 0.002), but no association. Both linkage and association tests were negative for H. The combined phenotype of having VV and H did not show any evidence of linkage or association. Conclusion: These results demonstrate VV and H to be heritable, related conditions, and the data strongly suggest FOXC2 to be implicated in the development of VV in the general population.